Kesantunan Deklaratif: Kajian Sosiopragmatik Kasus di Kecamatan Luas Kabupaten Kaur - Reni Kusmiarti; Ira Yuniati; Reva Junita Sari (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The aim is to describe declarative politeness (Sociopragmatic Study of Cases in District of Kaur Regency). The method used in this research is descriptive qualitative method. The data in this study were declarative actions of the Kaur community which contained the politeness of various situations and various speech partners which contained politeness in language. The source of data in this study is the community in the Kecamatan Kecamatan Kaur Regency. Data collection techniques using the technique of recording, recording, see competent involvement (SBLC), see competent involvement (SLC). Data analysis techniques, namely transcribing recorded data, identifying data, classifying data, analyzing, interpreting, concluding. The results showed that declarative acts were found to fulfill politeness based on the principle of politeness, namely 1) maxim of wisdom, 2) maxim of generosity, 3) maxim of appreciation, 4) maxim of simplicity, 5) maxim of consensus, and 6) maxim of sympathy. Conclusion, declarative speech acts of society have fulfilled politeness based on the principle of politeness. Keywords: Sociopragmatics, Politeness, Declarative Politeness